A Halogen‐Free and Flame‐Retardant Sodium Electrolyte Compatible with Hard Carbon Anodes (Adv. Mater. Interfaces 23/2021). Issue 23 (8th December 2021) - Colbin, Lars Olow Simon; Mogensen, Ronnie; Buckel, Alexander; Wang, Yong‐Lei; Naylor, Andrew J.; Kullgren, Jolla; Younesi, Reza
Abstract : Halogen‐Free and Flame‐Retardant Electrolyte for Sodium‐ion Batteries Apart from achieving a greater understanding of fluorine‐free electrolytes, it is essential to create safer electrolytes for the state‐of‐the‐art sodium‐ion batteries. In article number 2101135, Lars Olow Simon Colbin, Reza Younesi, and co‐workers demonstrate that using triethyl phosphate (TEP) with sodium bis(oxalato)borate (NaBOB) as the electrolyte will help to achieve this goal. Imagine if battery electrolytes could also help to fight fires, rather than fueling them—the case today.